2019
DOI: 10.18844/gjflt.v9i1.4068
|View full text |Cite
|
Sign up to set email alerts
|

The impact of CLIL implementation on Lebanese students’ attitudes and performance

Abstract: Content and language integrated learning (CLIL) has been verified as an effective pedagogical approach by a lot of research studies carried out in many European countries. However, modest attempts have been made to prove its efficacy in Lebanon, where English Language is taught in many schools and universities as a first foreign language. The participants (n = 21) were first year university students enrolled in the Faculty of Pedagogy at the Lebanese University and majoring in teaching Math at elementary schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Interviews with students who dropped out of CLIL stream revealed that their language proficiency, motivation and learning styles were behind their decision to leave the program since they felt that they were lagging behind the rest of the class. Apsel (2012) recommends evaluating these students' experiences to improve bilingual education programs (see also EL-Daou & Abdallah (2019).…”
Section: Misconception 2: Newcomers To a New Country Learn The National Language More Slowly Than Local Peoplementioning
confidence: 99%
“…Interviews with students who dropped out of CLIL stream revealed that their language proficiency, motivation and learning styles were behind their decision to leave the program since they felt that they were lagging behind the rest of the class. Apsel (2012) recommends evaluating these students' experiences to improve bilingual education programs (see also EL-Daou & Abdallah (2019).…”
Section: Misconception 2: Newcomers To a New Country Learn The National Language More Slowly Than Local Peoplementioning
confidence: 99%